Kinetic post-match fatigue in professional and youth soccer players during the competitive period - Djaoui, L.; Diaz-Cidoncha Garcia, J.; Hautier, C.; Dellal, A. (Asian Journal of Sports Medicine, 2016)
Background: No previous research has analysed kinetic fatigue of elite adult players and elite youth players during the competitive period..